Lexical-Semantic Features of Astronomical Terminology in the English Language (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
This article explores the lexical-semantic features of astronomical terminology in the English language, focusing on how specialized vocabulary in the field of astronomy functions within the broader linguistic system. The study examines the ways in which astronomical terms, such as celestial bodies, phenomena, and concepts, are formed, defined, and categorized in English. It highlights the role of metaphor, analogy, and etymology in the development of these terms, as well as their semantic shifts over time. Through this analysis, the article provides insights into the evolving nature of scientific language and its impact on knowledge dissemination in the field of astronomy.